Preskušanje gredi kolesnih dvojic na dizelskih motornih vlakih - Grum, Janez (Strojniški vestnik, 1999)
The present paper treats the testing of axles in wheel and axle sets of diesel-engined trains;attention is devoted both to theoretical and to practical work. First, the characteristics of ultrasonic probe were measured on an aluminium block by means of elektrodynamics probes. To this end we had at our disposal unserviceable axles of wheel and disassembled axle sets, where at individual critical points it was possible to simulate defects at various depths. On the basis of the defects, the applicability of individual ultrasonic probes at the shorter and longer side of the gear wheel of the driving axle from different fields, and with the apparatus setting at 1.5 and 2.5m. Each of the variants selected was recorded for subsequent analysis of the results. Finally, based on the procedures selected, the geometries of the known types of ultrasonic paths were calculated for comparison with the results of the experimental work.
Keywords: vlaki motorni(dieselski); preskušanje gredi; preskušanje ultrazvočno; analize poškodb; vlaki; gredi; testiranje; preskušanje